2017
DOI: 10.1093/aje/kwx159
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress and Its Relationship With Chronic Medical Conditions and Multimorbidity Among 229,293 Community-Dwelling Adults in 44 Low- and Middle-Income Countries

Abstract: This study assessed the association of chronic conditions and multimorbidity with perceived stress among community-dwelling adults in 44 low-and middle-income countries. Data were analyzed from the World Health Survey (2002)(2003)(2004) (18.29, 22.05) respectively. The associations with perceived stress were significantly stronger among the poorest for arthritis, asthma, diabetes, edentulism, and ≥4 chronic conditions. Our data suggest that a range of chronic conditions and multimorbidity are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 43 publications
3
62
0
5
Order By: Relevance
“…In this study, in both genders, the chance of membership in subclasses 1 through 3 increased with age. It is evident that chronic conditions and multimorbidity typically increase with age 50 . Authors state that age is related to the duration of exposure to risk factors 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, in both genders, the chance of membership in subclasses 1 through 3 increased with age. It is evident that chronic conditions and multimorbidity typically increase with age 50 . Authors state that age is related to the duration of exposure to risk factors 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Research has also started to consider the mental or emotional health burden of multimorbidity, such as perceived stress 14 , a state in which one perceives their life situations stressful 15 . The relationship between some single chronic conditions and perceived stress has been investigated to date, partly driven by the potential deleterious influence of stress on the patient's treatment outcomes and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important research gap given that a previous national Danish study identified that perceived stress may contribute to the heightened mortality in those with multimorbidity. 11 Previous research has suggested that multimorbidity is high in LMICs 14,20 and perceived stress levels are high due to considerable economic, environmental and health uncertainties, including less access to physical health care. Thus, this adds to the pressing need to explore this relationship within this context in older adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals requiring rehabilitation, whether due to developmental, acquired, or degenerative conditions, often experience co-occurring mental health conditions. This is due to the high prevalence of mental health problems and psychiatric disorders in the general population (Antunes et al, 2018, de Jonge et al, 2017 as well as to stressors (Vancampfort et al, 2017) and biological changes related to the various health-related conditions requiring rehabilitation (Ferro et al, 2017) . However, outside of psychiatric rehabilitation (Hutchison et al, 2017) , mental health assessment (MHA) is not always at the forefront of rehabilitation practice (Scanlan et al, 2017) .…”
Section: Introductionmentioning
confidence: 99%